Atlas‐guided brain projection tracts: From regions of interest to tractography 3D rendering - Dauleac, Corentin; Mertens, Patrick; Frindel, Carole; Jacquesson, Timothée; Cotton, François (Journal of anatomy, 2025)
The use of diffusion tensor imaging (DTI) has seen significant development over the last two decades, in particular with the development of the tractography of association tracts for preoperative planning of surgery. However, projection tracts are difficult to differentiate from one another and tractography studies have failed to reconstruct these ascending/descending pathways from/to the spinal cord. The present study proposes an atlas of regions of interest (ROIs) designed specifically for projection tracts tractography. Forty‐nine healthy subjects were included in this prospective study. Brain DTI was acquired using the same 3 T MRI scanner, with 32 diffusion directions. Distortions were corrected using the FSL software package. ROIs were drawn using the anterior commissure (AC)–posterior commissure (PC) line on the following landmarks: the pyramid for the corticospinal tract, the medio‐caudal part of the red nucleus for the rubrospinal tract, the pontine reticular nucleus for corticoreticular tract, the superior and inferior cerebellar peduncles for, respectively, the anterior and posterior spinocerebellar tract, the gracilis and cuneatus nucleus for the dorsal columns, and the ventro‐posterolateral nucleus for the spinothalamic tract. Fiber tracking was performed using a deterministic algorithm using DSI Studio software. ROI coordinates, according to AC–PC line, were given for each tract. Tractography was obtained for each tract, allowing tridimensional rendering and comparison of tracking metrics between tracts. The present study reports the accurate design of specific ROIs for tractography of each projection tract. This could be a useful tool in order to differentiate projection tracts at the spinal cord level. The present study proposes an atlas of regions of interest (ROIs) designed specifically for projection tracts tractography. ROIs were drawn using the anterior commissure (AC)–posterior commissure (PC) line. Fiber tracking was performed using a deterministic algorithm using DSI Studio software. ROI coordinates, according to AC‐PC line, were given for each tract. Tractography was obtained for each tract, allowing tridimensional rendering and comparison of tracking metrics between tracts.